Influence of family functioning on mental health of dual earner commuter couples in Malaysia - Pai, Farah Syuhada; Arshat, Zarinah; Ismail, Zanariah; Ahmad Shahril, Nurul Saidatus Shaja’ah (Academia Industry Networks, 2020)
Family functioning may affect developmental of each individual in the family. This study determines the relationship between family functioning and mental health. This cross sectional study was conducted among 90 couples of dual-earner commuter in Malaysia. The couples of dual earner commuter completed socio-demographic, family functioning and mental health questionnaires. The results of the study show that cohesion affects mental health positively. Meanwhile, adaptation affects mental health negatively due to changes in the family structure and burden of carrying multiples role in the same time. Notably, there was no significance difference in perception of family functioning and mental health between husbands and wives of dual-earner commuter couples in the current study.